2019
DOI: 10.1371/journal.pone.0221552
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pharmaceutically treated depression and treatment resistant depression in South Korea

Abstract: Background The epidemiology of pharmaceutically treated depression (PTD) and treatment resistant depression (TRD) is largely unknown in South Korea. The aim of this study was to develop a greater understanding of the characteristics of PTD and TRD in nearly the entire adult population in South Korea using the Health Insurance Review and Assessment Service (HIRA). Method Diagnostic codes and prescription data for South Korean adults were extracted from the HIRA. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In terms of psychiatric comorbidities, the TRD population was observed to have an increased risk of comorbid “Neurotic, stress-related and somatoform disorders” (ICD-10 F40–F48; see S6 Table in S2 File ) compared with the non-TRD population. This finding is in line with the results of several previous studies [ 2 , 8 , 20 , 35 , 39 , 49 , 50 , 58 ]; however, Perugi et al reported an almost identical prevalence of anxiety disorders in patients with MDD with and without TRD [ 29 ]. Conversely, Gronemann et al reported that patients with depression with comorbid anxiety had a lower risk of TRD compared with patients without comorbid anxiety, after adjustment for other measures of depression severity [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of psychiatric comorbidities, the TRD population was observed to have an increased risk of comorbid “Neurotic, stress-related and somatoform disorders” (ICD-10 F40–F48; see S6 Table in S2 File ) compared with the non-TRD population. This finding is in line with the results of several previous studies [ 2 , 8 , 20 , 35 , 39 , 49 , 50 , 58 ]; however, Perugi et al reported an almost identical prevalence of anxiety disorders in patients with MDD with and without TRD [ 29 ]. Conversely, Gronemann et al reported that patients with depression with comorbid anxiety had a lower risk of TRD compared with patients without comorbid anxiety, after adjustment for other measures of depression severity [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
“…As depressive episodes in the context of bipolar disorder are less responsive to AD treatment compared with those in MDD, the inclusion of patients with unidentified bipolar (spectrum) disorder could potentially distort the frequency of TRD [ 19 , 59 61 ]. With regard to somatic comorbidities, previous studies have reported conflicting results [ 8 , 18 , 34 , 35 , 37 , 39 , 49 , 50 , 58 , 62 , 63 ]. Within this study, we detected a significantly higher risk of autoimmune diseases, thyroid gland diseases, and cardio- and cerebrovascular disorders in patients with TRD compared with the non-TRD group.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that psychiatrists might prescribe low doses of TCAs to minimize its known harmful effects on CVDs while preserving its clinical effect on depression. Kim et al reported that it is common for psychiatrists in Korea to prescribe antidepressants in doses less than the minimum effective daily dose due to their side effects ( Kim et al, 2019 ). Our results showed that TCA use was associated with an increased risk of MACEs even at its low doses, <0.5 DDD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates of TRD prevalence, extracted from insurance databases, among pharmaceutically treated depressive patients ranged from 4.2% in Korea to 20.9% in Taiwan. 10 , 11 Given the lack of standardized definition of TRD, it is not surprising to observe wide-ranging differences in TRD prevalence estimates. The landmark study, Sequenced Treatment Alternatives to Relieve Depression (STAR*D), was one of the first significant studies which helped to better characterize the patients with TRD.…”
Section: Introductionmentioning
confidence: 99%